2017
DOI: 10.21276/aimdr.2017.3.5.pm1
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Abnormalities in Petrol Pump Workers in Suburban Areas of Chennai

Abstract: Background: The response of the human lungs to exposure to various particles like seen in atmospheric pollution, work place, various gases, have been studied in different populations by various studies. The pollution level in Chennai city is moderate whereas it is quite high in the suburbs of Chennai. Aim: To understand the effect of petrol and diesel vapours on lungs in persons working at petrol pump stations in the suburbs of Chennai through Spirometry. Methods: This study was conducted at 20 Petrol pumps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Smokers develop abnormalities in pulmonary functions more frequently than non-smokers [10,12,15] . Early response of the lungs to smoking begins in small airways [4,6] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Smokers develop abnormalities in pulmonary functions more frequently than non-smokers [10,12,15] . Early response of the lungs to smoking begins in small airways [4,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Determination of pulmonary functions is highly dependent upon the duration and amount of tobacco consumed. Considering the economic status, bidi smokers predominate in the lower income groups while in the high socio-economic status group, cigarette smoking is more common [14,12,15] . Our study showed that almost all the smokers smoked bidi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations